About overyielding with mixed cultures in batch processes. Issue 26 (2019) - Harmand, J.; Rapaport, A.; Nidelet, T.
Abstract: This paper investigates - via modeling - several possible explanations of overyielding observed in mixed cultures cultivated in batch reactors. It is first shown that the classical model of competition of N species for a single resource cannot explain such overyielding. Then, three hypotheses are introduced and discussed at the light of numerical simulations.